2018
DOI: 10.3390/cells7070069
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Cell Recruitment and Behavior within the Tumor Microenvironment Using Advanced Intravital Imaging Approaches

Abstract: Recent advances in imaging technology have made it possible to track cellular recruitment and behavior within the vasculature of living animals in real-time. Using approaches such as resonant scanning confocal and multiphoton intravital microscopy (IVM), we are now able to observe cells within the intact tumor microenvironment of a mouse. We are able to follow these cells for extended periods of time (hours) and can characterize how specific cell types (T cells, neutrophils, monocytes) interact with the tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Within tumour vessels intravital imaging approaches to visualise the leucocyte-endothelium interactions, Turk and co-workers identified few crawling Ly6G + neutrophils in the venules while CD8 + T cells crawled in both collecting and post-capillary venules, indicating different leucocyte subpopulations may crawl along distinct vascular structures or components within the TME (extracellular matrix, collagen, etc.) [ 75 ]. Further, it was also revealed that intratumoral leucocytes of both lymphoid and myeloid origin showed an active non-altered intraluminal migration in the mouse hepatocellular cancer model, and the locomotion velocity of leucocytes was also cell number-independent [ 76 ].…”
Section: Leucocyte Traffickingmentioning
confidence: 99%
“…Within tumour vessels intravital imaging approaches to visualise the leucocyte-endothelium interactions, Turk and co-workers identified few crawling Ly6G + neutrophils in the venules while CD8 + T cells crawled in both collecting and post-capillary venules, indicating different leucocyte subpopulations may crawl along distinct vascular structures or components within the TME (extracellular matrix, collagen, etc.) [ 75 ]. Further, it was also revealed that intratumoral leucocytes of both lymphoid and myeloid origin showed an active non-altered intraluminal migration in the mouse hepatocellular cancer model, and the locomotion velocity of leucocytes was also cell number-independent [ 76 ].…”
Section: Leucocyte Traffickingmentioning
confidence: 99%
“…The most powerful research tool available to characterize neutrophil trafficking in vivo is intravital microscopy (IVM), which involves surgical exposure of an organ of interest (in a live anesthetized animal) and direct visualization with a microscope to observe neutrophil behavior in blood vessels and tissues [ 5 ]. Within the field of immuno-oncology, IVM has proven particularly powerful to study the trafficking and function of neutrophils within tumors as well as their contribution to cancer metastasis [ 6 , 7 , 8 , 9 ]. In this section, we provide a primer overview of the most common contemporary IVM modalities (confocal and two-photon imaging) and explore emerging IVM technologies that will expand our ability to discover new aspects of neutrophil biology in vivo.…”
Section: Seeing Is Believing—in Vivo Imaging Of Neutrophil Trafficking and Functionmentioning
confidence: 99%
“…When pairing these fluorescent transgenic mice with an intravital microscope, it becomes possible to delve deep underneath dense tissue and potentially observe megakaryopoiesis and changes in ploidy and proplatelet formation and release into the blood stream (87,164). Fluorescently-labeled platelets have enabled studies of platelet migration and platelet interactions with other blood cells, in a number of physiology scenarios, including inflammation (139), infection (165), and cancer (166).…”
Section: Hemostasis and Thrombus Formation In Its Natural Microenviromentioning
confidence: 99%
“…The concept of in vivo IFC systems was developed to count, characterize, and image biological cells flowing in a living organism (in this case a mouse) at different time points, thus providing longitudinal information of biological events. The in vivo flow cytometer was first used to quantify the circulation lifetime of different tumor cells and monitor apoptotic cells in circulation (166,207,208) with single cell sensitivity. However, existing in vivo IFC approaches are limited by technological challenges that restrict 2D regions of interest to superficial layers of tissue, preventing the experimental interrogation of cellular and molecular events in major blood vessels.…”
Section: In Vivo Imaging Cytometrymentioning
confidence: 99%